Increased seawater temperature and decreased dissolved oxygen triggers fish kill at the Cocos (Keeling) Islands, Indian Ocean - Hobbs, Jean-Paul; McDonald, C. (Blackwell Publishing, 2010)
At the Cocos (Keeling) Islands in the north-eastern Indian Ocean >592 fishes from at least 11 species died in a series of events in December 2007, January and February 2008 and April 2009. The dead fishes were from a wide range of taxonomic families, indicating that conditions exceeded the tolerances of a broad array of species. The 2007–2008 die-off events occurred on the warmest and calmest days of a significantly warmer and calmer summer. Fishes died in the southern inshore areas of the coral atoll lagoon at survey sites where seawater temperature was highest (33–35° C) and dissolved oxygen was lowest (1·4–1·8 mg l-1). The water temperature at these fish-kill survey sites (33–35° C) was significantly warmer than previous years (1997 to 2005, mean ±s.e. = 28·7 ± 0·1° C). Fishes probably died because they were unable to obtain the additional oxygen required for metabolism at higher temperatures. Repeated die-off events over the last 130 years indicate that some fishes have not yet adapted to rises in seawater temperature. This study provides empirical evidence to support suggestions that differences in physiological tolerances to increasing sea temperatures may be important in determining the structure of future coral-reef fish communities with respect to climate change.